Femtosecond laser inscribed gratings for monolithic MIR fiber lasers - Theodosiou, Antreas; Aubrecht, Jan; Kanagaraj, Nithyanandan; Peterka, Pavel; Honzátko, Pavel; Stassis, Andreas; Kalli, Kyriacos (My University, 2019)
We present our recent developments regarding monolithic fibre lasers, incorporating gratings as reflectors and polarizing elements via the plane-by-plane femtosecond laser inscription method. Designs are considered for continuous and pulsed laser operation in the mid-infrared wavelength range.
Keywords: Monolithic; MIR fiber lasers